2021
DOI: 10.3847/2041-8213/abf3c9
|View full text |Cite
|
Sign up to set email alerts
|

Binarity as the Origin of Long Secondary Periods in Red Giant Stars

Abstract: Long secondary periods (LSPs), observed in a third of pulsating red giant stars, are the only unexplained type of large-amplitude stellar variability known at this time. Here we show that this phenomenon is a manifestation of a substellar or stellar companion orbiting the red giant star. Our investigation is based on a sample of about 16,000 well-defined LSP variables detected in the long-term OGLE photometric database of the Milky Way and Magellanic Clouds, combined with the mid-infrared data extracted from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…We ensured this was not an alias of the shorter period by checking that the secondary peak remains after we removed the primary pulsation from the data. Furthermore, the 41-year pulsation period is consistent with long sec-ondary periods detected in several AGB stars (Wood et al 1999;Soszyński et al 2021). Henceforth, we refer to the "pulsation" as the first 372-day period and "variability" as the long-term variability of 41 years.…”
Section: Stellar Pulsationsupporting
confidence: 82%
“…We ensured this was not an alias of the shorter period by checking that the secondary peak remains after we removed the primary pulsation from the data. Furthermore, the 41-year pulsation period is consistent with long sec-ondary periods detected in several AGB stars (Wood et al 1999;Soszyński et al 2021). Henceforth, we refer to the "pulsation" as the first 372-day period and "variability" as the long-term variability of 41 years.…”
Section: Stellar Pulsationsupporting
confidence: 82%
“…The variability of LPVs is not only associated with stellar oscillations. In particular, LPVs often display so-called long secondary periods (LSPs) that form sequence D in the PLD and whose origin is still a matter of debate (e.g., Wood 2000;Olivier & Wood 2003;Wood et al 2004;Derekas et al 2006;Soszyński 2007;Nicholls et al 2009;Stothers 2010;Takayama et al 2015;Saio et al 2015;Takayama & Ita 2020;Pawlak 2021;Soszyński et al 2021). As it is generally accepted that these periods are not due to pulsation, we aim to exclude them from the data set.…”
Section: Pulsation Mode Identificationmentioning
confidence: 99%
“…Here we show that those remarks are genuine for a larger sample of HBSs in the LMC as well as for HBSs located toward the GB. Recently, Soszyński et al (2021) showed that LSP variables (sequence D) are systems that contain an RG and a stellar or sub-stellar companion. In combination with eclipsing and ellipsoidal stars (sequence E), they form a group with a wide range of periods (from a few days to about three years), for which the brightness changes are driven mainly by the interactions between the components of the binary system.…”
Section: Period-amplitude Diagramsmentioning
confidence: 99%

Photometric Analysis of the OGLE Heartbeat Stars

Wrona,
Kołaczek-Szymański,
Ratajczak
et al. 2021
Preprint